Influence of Education on Unemployment Rate and Incomes of Residents. (12th February 2015) - Lavrinovicha, Ilga; Lavrinenko, Olga; Teivans-Treinovskis, Janis
Abstract: The importance of education in the modern world is increasing as the most serious factor in the formation of a new quality of economy and society in common. It's role is constantly growing along with the growing influence of human capital. The article examines the impact of education on the unemployment rate and the amount of income of residents of Latvia in the period from 2002 to 2013. Differences in the amount of income and in the existence of job, which are determined by the level of education, are analyzed by the authors from the position of human capital as well as from the level of social and institutional relations. Methods of frequency, correlation and regression analysis are used in the research.